Novel Use in Psychological Counseling and Guidance Education: An Analysis of the Novel of "Oblomov" in Terms of Reality Therapy - Hazel DURU (Anı Publishing, 2021)
Novels are literary works and contain many psychological elements. Analyzing the attitudes of the characters, reflecting them, depicting their life frame and experiences are among the most important features of the novels. At this point, it is not surprising that there is a relationship between novels and psychology. In this study, it was aimed to examine the work named "Oblomov" in terms of reality therapy in order to show the use of novel in psychological counseling and guidance education. Reality therapy is based on the necessity of taking responsibility and the choices individuals make throughout their lives. Basic requirement, choice and responsibility, quality world-picture album, being here and now, successful and failure identity, etc. concepts constitute some of the basic concepts of reality therapy. The study was carried out with an analytical research model. In addition to being among the important classics of World Literature, the novel discussed in this study can be examined in terms of reality therapy because it deals with a character that has never met the need for freedom, does not value himself, and has difficulty in fulfilling his duties in life. This research has shown that the novel "Oblomov" can be used as an additional resource to understand the concepts of reality therapy and to illustrate the concepts.